In silico molecular mechanism of cannabigerol as a cyclooxygenase-2 inhibitor - Muhammad Abdullah Shah; Syed Muhammad Abdullah; Muhammad Azim Khan; Hazrat Amin; . Roohullah (Bangladesh Pharmacological Society, 2013)
Discovery of new cyclooxygenase-2(COX-2) inhibitors is a major area in anti-inflammatory drug discovery. Cannabigerol is a cannabinoid, which is recently discovered as a new COX-2 inhibitor. So far no work has been done to explore in depth mechanistic insights to understand its mechanism and binding mode. In the current investigation, molecular docking simulations were performed to explore its binding mode and is molecular interactions with the ligand binding site of COX-2 enzyme. Cannabigerol showed multiple molecular contacts with active of COX-2 especially withArg120, Tyr355, and Met522. Hydrogen bonding, dipole-dipole and hydrophobic interactions were the key attractive forces involved in macromolecular contacts. Molecular modifications in Cannabigerol are discussed, which can lead to further improvement of the ligand as a new lead compound against COX-2 enzyme.